Analysis of Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) Levels in Rats Given Jamu Cekok Decoction - Risya Alfhadillah; Puji Astuti; Sari Rahmayanti; Virhan Novianry (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Jamu cekok is a traditional medicine used by Indonesians, especially children to increase appetite. However, the safety test of jamu cekok on liver function using Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) as parameters has never been evaluated. This study aimed to determine the effect of jamu cekok on liver function by assessing SGOT and SGPT levels in rats subjected to acute toxicity. The study employed an analytical experimental design with the OECD 425 method. The test rats used were 12, divided into a control group, a 2000 mg/kg BW treatment group and a 5000 mg/kg BW treatment group. The treatment of jamu cekok decoction was given once on the first day of the acute toxicity test and was observed for 14 days. SGOT and SGPT levels were measured and analyzed using one-way ANOVA to assess differences between groups. Through this study, observations of behavior and body weight over the 14 days showed no signs of toxicity or mortality. The LD50 value was determined to be greater than 5000 mg/kg BW, which is categorized as practically non-toxic. One-way ANOVA followed by Tukey’s HSD post hoc tests revealed no significant differences in SGOT levels between the control and treatment groups (p>0,05). Similarly, SGPT levels also showed no significant difference (p>0,05) between groups. These findings indicate that he administration of jamu cekok at a dose of 2000 mg/kg BW and 5000 mg/kg BW does not induce toxic effects on liver function, as reflected by SGOT and SGPT measurements.